Corporate reporting and company law - Villiers, Charlotte (Cambridge studies in corporate law., 2006)
This book explores the main disclosure requirements of companies in their reporting activities, and seeks to bring together the main features of the reporting system. The book considers the theoretical basis of the corporate reporting system and describes the regulatory framework for that system.